Running Compression Garments Design Using Biomass Graphene Modified Fiber (Journal of Fiber Bioengineering and Informatics, 2019)
This Paper elaborates the performance of biomass graphene modified fibers and the importance of muscle protection during running. Then, it analyzes the muscle contraction and relaxation during the running process and the human thermal-wet comfort. According to the needs, we conduct the human body partition and enter the design of the compression garments. During the design process, the functionalities of graphene modified fibers and the advantages of seamless knitting are explained. The function and technique are integrated to ensure the scientific and rationality of compression garments design. Finally, the detailed design concept are illustrated.